Mouse DNA primase plays the principal role in determination of permissiveness for polyomavirus DNA replication. - Eki, T (1991)
We have investigated the species-specific replication of polyomavirus DNA in the cell-free system that was established previously (Y. Murakami, T. Eki, M. Yamada, C. Prives, and J. Hurwitz, Proc. Natl. Acad. Sci. USA 83:6347-6351, 1986). Extracts from various species of cells supported polyomavirus DNA replication in a species-specific manner that was consistent with the host range specificity of polyomavirus; extracts prepared from mouse and hamster cells were active, whereas extracts prepared from human, monkey, and insect cells were inactive. The addition of DNA polymerase alpha-primase purified from mouse cells induced the replication of polyomavirus DNA in a cell-free system containing polyomavirus large tumor antigen and nonpermissive cell extracts, such as human and insect cell extracts. Isolated mouse DNA primase alone also induced polyomavirus DNA replication in human cell extracts but not in insect cell extracts, indicating that mouse DNA primase plays the principal role in determining permissiveness for polyomavirus DNA replication.